Development and quality characterization of mutton snack. Issue 6 (9th November 2015) - Talukder, S.; Mendiratta, S.K.; Soni, Arvind; Singh, Tarun Pal; Chhangte, Lalchamliani; Kumar, R.R.; Goswami, Meena; Malav, O. P.; A, Irshad
Abstract : Purpose: – The aim of this study was to explore the feasibility of formulation, quality characterization and acceptability of rice flour- and black gram flour-incorporated mutton snack among consumers. Cereal-based snacks, which have very less nutritional value, are highly popular among Indian consumers. Malnutrition and protein deficiencies can be overcome by supplying nutrient-dense meat-incorporated cereal-based snacks to them. On this background, it was planned to incorporate easily available sheep meat to popular snack to improve the nutritional quality, acceptability and functionality of traditional snack. Design/methodology/approach: – Mutton-based snack formulation was standardized; rice flour (Treatment-I [T-I]), black gram flour (Treatment-II [T-II]) and their combination (Treatment-III [T-III]) were used along with lean meat for the preparation of mutton snack. Microwaving and frying process of cooking was applied, and various physicochemical and sensory properties of both raw and cooked snack were evaluated. Findings: – Emulsion stability and expansion percentage increased significantly ( p < 0.05) in all treatment products in both cooking process except in T-III. Significant ( p < 0.05) decrease in protein percentage and increase in fat percentage has been recorded in all treatments and cooking process in comparison to control. The overall acceptability scores increased significantly in all the treatments except T-III in comparison to control. On the basis of physicochemical and sensory attributes the microwaved black gram flour-added mutton snack (T-II) was adjudged as most acceptable and was stored for a period of 45 days at ambient temperature. It was concluded that optimized product could be stored at room temperature in LDPE pouches for 45 days without marked deterioration in quality on the basis of evaluations of physicochemical (pH and thiobarbituric acid reacting substances value) and microbiological parameters (total plate count, coliform count and yeast and mould count). Research limitations/implications: – Future research may benefit from attempting to modify shelf life of the snack in room temperature by modifying storage and packaging condition. Originality/value: – Although incorporation of meat in cereal-based traditional snack and the effect on its quality characteristics have been extensively examined, limited research has focused on this aspect. Additionally, limited qualitative research has examined the storage characteristics of meat-incorporated snack at room temperature in eating quality context.